PERBEDAAN HASIL BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA PENDIDIKAN BIOLOGI MENGGUNAKAN PENDEKATAN PEMBELAJARAN DEDUKTIF DAN INDUKTIF PADA KONSEP EKOSISTEM - Liah Badriah (Bioedusiana: Jurnal Pendidikan Biologi, 2016)
This study aimed at investigating the differences between result study and critical thinking ability of biology students employing deductive and inductive learning approaches based on the ecosystem concept. This study uses comparative research, particularly posttest control group design. Besides, the population of this study the entire Second Semester Students of Biology Education Department, Faculty of Educational Sciences and Teachers’ Training, Siliwangi University.Moreover, the sample of this study is two classes taken randomly by utilizing cluster random sampling with a total of 67students. In addition, technique of collecting the data was conducted by the posttest to the students in order to obtain the data about students’ final learning outcomes and applying rubric for the sake of identifying the students’ critical thinking abilities. Likewise, T-Test (the test using to compare the differences of two scores average) with (α) = 5% as the significant level was used. The result of the data analysis and hypothesis testing, the results showed that (1)There was a significant learning outcome of Biology students employing deductive and inductive learning approaches. (2) there was a significant level of biology students’ creative thinking ability applying deductive and inductive learning. As a result, deductive learning approach plausibly yielded better learning outcomes and Inductive learning approach obviously influenced the students’ critical thinking abilities.Key Words: Inductive learning approach, deductive learning approach, result study and critical thinking ability.